The Effect of Sorghum Grain on Ruminal Fermentation and Some Blood Parameters in Beef Cattle - Baran, M. S.; Yokus, B.; Gul, I.; Alp, M.; Sahin, N. (Medwell Online, 2008)
In this research, the effect of sorghum in beef cattle mixture feeds as energy source instead of wheat on ruminal fermentation and some blood parameters was investigated. In the experiment, 20 Holstein beef cattle of 1.5 years old, each weighing average 330 kg were used. The trial was done in 2 stages: the first stage was pre-experimental period for 2 weeks and the second stage was the main experimental period for 10 weeks, totally lasting twelve weeks. During the whole experimental period, isocaloric and isonitrogenic 2 diets were used. In control group, mixtures involved 27% wheat, but in experimental group 27% sorghum was used instead of wheat. Dried alfalfa hay was used as roughage. Both rations consisted of 80% concentrated feed and 20% roughage. The differences between the groups for ruminal fermentation parameters; rumen fluid pH, ammonia concentrations, total volatile fatty acids, acetate, propionate, butyrate levels were not significant (p>0.05). In both groups differences, at the beginning and middle of the trial period for blood serum parameters (total protein, glucose, albumin, Ca, Na, P, K, Zn, Cu, Fe, Mg), were not significant, but at the middle and end of the trial, the differences between the groups was significant for blood serum Se levels (p<0.05). Trial results indicated that sorghum grain could be used instead of wheat as an economical energy source in beef cattle rations.
Keywords: Sorghum; beef cattle; ruminal fermentation; blood parameters